Pengaruh Pupuk Kascing dan Pupuk P terhadap Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) - Muhammad Fauzi; Hapsoh Hapsoh; Erlida Ariani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to determine the effect of Kascing fertilizer and P fertilizer and the best combination in improving growth and yield of shallots. This research has been conducted in the experimental garden of Agriculture Faculty University of Riau from May until July 2017. The research was conducted experimentally by using Completely Randomied Design (RBD) with two factors and three replications. First factor was giving kascing fertilizer with three levels which is 2 kg per 2m2,4 kg per 2 m2 and 6 kg per 2 m2. The second factor was giving P fertilizer with three levels which is 13 g per 2 m2,26 g per 2 m2 and 39 g per 2 m2. Parameters observed were plant height, number leaves per clump and number bulbs per clump, bulbs diameter, weight of fresh bulbs per 2 m2, and weight of tuber worth to save per2 m2. The result showed that kascing fertilizer and P fertilizer had no effect to all of parameters which is plant height, number leaves and number bulbs, bulbs diameter, weight of fresh bulbs, and weight of tuber worth to save . Kascing fertilizer had effect to all parameters except number leaves per clump and number bulbs per clump, meanwhile P fertilizer had no effect to all parameters except number of leaves per clump.Giving 2 kg per 2 m2 kascing fertilizer and giving 13 g per 2 m2 P fertilizer been able to improve plant height, number leaves and number bulbs, bulbs diameter, weight of fresh bulbs, and weight of tuber worth to save shallots varieties Bima Brebes.Keyword:shallot, kascing fertilizer, P fertilizer